Nanotechnologies as a Basis for Realization of the Paradigm for National Economic Development. (Economics and region, 2017)
UDC [330.332+330.341.1]«71»(477) Bondar-Pidhurska, PhD (Economics), Associate Professor. High Educational Institution Accountable to UCU  (Ukrainian  Cooperative  Union)  «Poltava   University   of   Economics  and Trade». Hliebova, PhD (Economics), Associate Professor. Poltava National Technical Yurii Kondratiuk University. I. Khomenko, Нead of the Department of Industrial Property Researches. Center of Intellectual Property and Technology Accountable to NAS of Ukraine. Nanotechnologies as a Basis for Realization of the Paradigm for National Economic Development. Building on the analysis carried out by foreign and domestic experience, nanotechnologies as a basis for implementation the paradigm of national economic development and effective technologies transfer were considered. This is an important condition for its implementation, based on the methodology of systematic and integrated approaches both. Besides it’s an instrument of satisfying the vital interests of the population in the plane "person - society - state - economy - environment". The concept of industry’s innovative activity development in the context of sustainable satisfying of population’s vital interests was developed. This creates a solid foundation for the realization of a new paradigm of Ukraine's economy development and contributes to social stability in the country. The conceptual features and main problems in the context of realization of paradigm of national economic development were singled out. There are substantiated in the article practical applications of nanotechnologies as the most important strategic direction of high-tech industries development, innovative transformation of industry, an instrument of satisfying the vital interests of population. Results of foresight evaluation of priority innovative technologies of 21th century in EU, USA and Japan in 2015–2030 in the context of satisfying of vital interests of population in Ukraine were investigated. In the plane of realization of paradigm of national economy development the concept of innovative activity of industry’s implementation in the context of satisfying of vital interests of population in Ukraine was proposed. Nanotechnologies as a basis of realization of national paradigm of economy development were positioned. There was substantiated that Ukraine has a future only with nanotechnologies and nanomaterials. This will not only solve the problem of quality, energy conservation and energy efficiency, but also create a competitive advantage for domestic producers in the long term. This emphasized the necessity of effective technology transfer and enforcement of intellectual property within the national economy. Conceptual and practical recommendations for future providing the useful implementation of paradigm of national economy development and improving the level of satisfaction of vital interests of population in Ukraine were proposed.Keywords: paradigm, national economy, nanotechnologies, nanomaterials, the vital interests of population.